Impacts of drought at different time scales on forest growth across a wide climatic gradient in north-eastern Spain - Pasho, Edmond; Camarero, J. Julio; de Luis, Martín; Vicente-Serrano, Sergio M. (Agricultural and Forest Meteorology, 2011)
We analyzed the impact of drought measured on different time-scales on radial growth of eight tree species during the period 1950–2005 growing across a wide climatic gradient encompassing semiarid Mediterranean woodlands and wet mountain forests in north-eastern Spain. A drought index (standardized precipitation index, SPI) at different time scales (1–48 months) was correlated with chronologies of ring width to determine the signiﬁcant time scale at which drought affected most tree growth. The ﬁndings indicated that the impact of drought on growth varied noticeably among species and sites. Two distinct patterns were clearly observed considering spatial and temporal differences in the response of species to drought. Species growing in xeric sites (Pinus and Quercus species and Juniperus thurifera) showed the highest responses to SPI time-scales of 9–11 months while those located in mesic sites (Abies alba, Pinus sylvestris) did respond more to SPI time scales shorter than 5 months. The SPI-growth correlations were signiﬁcant, although weak, up to 30 months in xeric sites while no consistent association was observed at higher time scales. Important seasonal differences were noticed in the SPI-growth associations. Species growing in xeric areas responded to spring-summer SPI while those distributed in mesic sites responded more to summer SPI. Our ﬁndings should be useful to understand forest responses to climate change, including an increasing frequency of severe droughts, and to adapt appropriate management strategies to mitigate the impact of drought on tree growth.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Dendrochronology; Drought; Forest growth; Impacts; NE Spain; Standardized precipitation index (SPI)